Proton conductivity of β-PCMOF2 in different temperatures and external electric fields: an insight from molecular dynamics simulation. (March 2020) - Farzi, N.; Rahimi, F.; Sabzyan, H.
Graphical abstract: β-PCMOF2 including 4 protons The protons have been shown with white color and the framework atoms with red (oxygen), yellow (sulfur), light blue (carbon), and dark blue (sodium). Highlights: Proton conductivity of β -PCMOF2 was calculated in different temperatures. Proton conductivity of β -PCMOF2 decreases with temperature. Grotthuss mechanism for proton conduction of β-PCMOF2 was recognized. Proton conductivity of β-PCMOF2 under different electric fields was investigated. ABSTRACT: Proton conductivity of Na3 ( 2, 4, 6-trihydroxy-1, 3, 5-benzenetrisulfonate ) framework ( β -PCMOF2) is studied in anhydrous and humid conditions using molecular dynamics simulation in the temperature range of 303-423 K. To obtain results compatible with experiments force field parameters for proton is adjusted. The Grotthuss mechanism for proton conduction of β-PCMOF2 is proved by obtaining an activation energy in the range of ( − 0.261, − 0.101 eV). The effect of the electric field on proton conductivity is also investigated. Proton conduction is reduced with temperature which is in agreement with the experiments. The RDF plots obtained in the absence of electric field and the effect of electric field on the proton MSD show that the protons transport through the oxygen atoms of sulfonate groups of the framework and their movements in the x and y directions are more than that in the z -direction. Simulations are carried out in the presence of protonated water and 1, 2, 4-triazole molecules rejected possibility of the vehicle.